Quantitative magnetic resonance spectroscopy of depression: The value of short-term metabolite changes in predicting treatment response - Wang, Ranchao; Shen, Yu; Li, Guohai; Du, Rui; Peng, Aiqin (Frontiers in Neuroscience, 2022)
Background: Although various prediction models of the antidepressant response have been established, the results have not been effectively applied to heterogeneous depression populations, which has seriously limited their clinical value. This study tried to build a more specific and stable model to predict treatment response in depression based on short-term changes in hippocampal metabolites. Materials and Methods: Seventy-four major depressive disorder (MDD) patients and 20 healthy controls in the test set were prospectively collected and retrospectively analyzed. Subjects underwent magnetic resonance spectroscopy (MRS) once a week during six weeks of treatment. Hippocampal regions of interest (ROIs) were extracted by using a voxel iteration scheme combined with standard brain templates. The short-term differences in hippocampal metabolites between and within groups were screened. Then, the association between hippocampal metabolite changes and clinical response was analyzed, and a prediction model based on logistic regression was constructed. In addition, a validation set (n=60) was collected from another medical center to validate the predictive abilities. Results: After 2-3 weeks of antidepressant treatment, the differences in indicators (tChowee0-2, tChowee0-3 and NAA week0-3) were successfully screened. Then, the predictive abilities of these three indicators were revealed in the logistic regression model, and the optimal prediction effect was found in d(tCho)week0-3-d(NAA)week0-3 (AUC=0.841, 95%CI=0.736-0.946). In addition, their predictive abilities were further confirmed with the validation set. Limitations: The small sample size and the need for multiple follow-ups limited the statistical ability to detect other findings. Conclusion: The predictive model in this study presented accurate prediction and strong verification effects, which may provide early guidance for adjusting the treatment regimens of depression and serve as a checkpoint at which the eventual treatment outcome can be predicted.